Statistical Physics Modelling of Dye Adsorption on Modified Cotton - M. Khalfaoui; M.H.V. Baouab; R. Gauthier; A. Ben Lamine (Adsorption Science & Technology)
Experimental adsorption isotherms for four anionic dyes (Acid Blue 25, Acid Yellow 99, Reactive Yellow 23 and Acid Blue 74) on to cationized cotton have been analyzed using a multilayer adsorption model. For such purpose, the double-layer model showed the best fit with a high correlation coefficient R 2 . The analytical expression of the model has been established from an application of the grand canonical ensemble of statistical physics. This method allowed an estimation of all the mathematical parameters in the model. Thus, the receptor site density and the half-saturation concentration have been related to physicochemical variables such as the chemical potential, the adsorption energy, the anchorage number, etc. A physical interpretation of the model parameters has been provided and some results relating to the adsorption process discussed.